Production of Organic Acids by Arbuscular Mycorrhizal Fungi and Their Contribution in the Mobilization of Phosphorus Bound to Iron Oxides - Andrino, Alberto; Guggenberger, Georg; Kernchen, Sarmite; Mikutta, Robert; Sauheitl, Leopold; Boy, Jens (Frontiers in Plant Science, 2021)
Most plants living in tropical acid soils depend on the arbuscular mycorrhizal (AM) symbiosis for mobilizing low accessible phosphorus (P), due to its strong bonding by iron (Fe) oxides. The roots release low-molecular-weight organic acids (LMWOAs) as a mechanism to increase soil P availability by ligand exchange or dissolution. However, little is known on the LMWOAs production by AM fungi (AMF), since most studies conducted on AM plants do not discriminate on the LMWOAs origin. This study aimed at determining whether AMF release significant contents of LMWOAs to liberate P bound to Fe oxides otherwise unavailable for the plant. Solanum lycopersicum L. plants mycorrhized with Rhizophagus irregularis were placed in a bicompartmental mesocosm, with P sources only accessible by AMF. Fingerprinting of LMWOAs in compartments containing free and goethite-bound orthophosphate and phytic acid were determined. To assess P mobilization via AM symbiosis, P content, photosynthesis, and the degree of mycorrhization were determined in the plant; while AM hyphae abundance were determined using lipid biomarkers. The results showing a higher shoot P content, along with a lower N:P ratio and a higher photosynthetic capacity, may be indicative of a higher photosynthetic P use efficiency, when AM plants mobilized P from less accessible sources. The presence of mono-, di-, and tricarboxylic LMWOAs in compartments containing goethite-bound orthophosphate and phytic acid points towards the occurrence of reductive dissolution and ligand exchange/dissolution reactions. Furthermore, hyphae grown in goethite loaded with orthophosphate and phytic acid exhibited an increased content of unsaturated lipids, pointing to an increase membrane fluidity in order to maintain optimal hyphal functionality and facilitate the incorporation of P. Our results underpin the centrality of AM symbiosis in soil biogeochemical processes, by highlighting the ability of the AMF and accompanying microbiota in releasing significant amounts of LMWOAs to mobilize P bound to Fe oxides.